The Disclosure Of A Spouse’s Disgrace Before And After Divorce: A Maqasid Al-shariah-based Legal Analysis Of The ‘spill The Tea’ And ‘exposing Ex’ Phenomenon - Muhammad Danish Irfan Mohd Azam; Muhammad Irfan Asyraf Ahmad; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
How humans communicate and interact with one another today has significantly evolved due to advancements in information and communication technologies, particularly affecting personal relationships. One adverse phenomenon arising from these changes is the trend of publicly exposing someone’s flaws or private matters on social media, notably involving former spouses, commonly known as “exposing ex.” This reflects shifts in social norms and brings various negative impacts from legal, ethical, and societal well-being perspectives. Thus, exposing a former partner’s shortcomings on social media is neither suitable for conflict resolution nor beneficial, as it inadvertently fosters slander, incites hatred, and leads to fractures within familial and community institutions. Additionally, it may strip marriages of their blessings and trigger greater harms, such as the rise in uncontrollable divorce cases, a deeply concerning trend. This study employs a qualitative approach, primarily involving content analysis of scholarly literature, current news, and opinions from Islamic scholars concerning disclosing personal faults. Findings demonstrate that revealing someone’s private issues, including those of former spouses, contradicts Islamic principles, emphasising dignity preservation, explicitly forbidding gossip (ghibah), and spying on personal shortcomings (tajsis). From a legal perspective in Malaysia, such actions constitute offences punishable under the Communications and Multimedia Act 1998 if found guilty of privacy infringement and defamation. Therefore, exposing former partners’ private matters should be recognised as a critical issue requiring stricter enforcement of laws to curb “spilling the tea” openly in the digital space.